2013
DOI: 10.1111/eff.12110
|View full text |Cite
|
Sign up to set email alerts
|

Marine migrations in anadromous brown trout (Salmo trutta). Fjord residency as a possible alternative in the continuum of migration to the open sea

Abstract: Technical University of Denmark, National Institute of Aquatic Sciences, Vejlsøvej 39; 8600; Silkeborg, Denmark.ABSTRACT. Partial migration is a common phenomenon in many fish species. Trout (Salmo trutta) is a partially migratory species where some part of the population migrate to the marine environment, while another remains in freshwater.In the years 2008 and 2009, a total of 159 wild sea trout smolts were tagged with acoustic and PIT tags in the river Villestrup (Denmark) to study the initial post-smolt m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 35 publications
4
39
3
Order By: Relevance
“…In contrast to our findings, an earlier study found that low body condition correlated with increased migration distance in sea trout, potentially for the purpose of maximizing feeding opportunities (Eldøy et al, 2015). Furthermore, home range size has been shown not to correlate with size for trout (Závorka, Aldvén, Näslund, Höjesjö, & Johnsson, 2015), and it has also been shown that migratory decisions in the fjord are not affected by size (del Villar-Guerra et al, 2014). Furthermore, home range size has been shown not to correlate with size for trout (Závorka, Aldvén, Näslund, Höjesjö, & Johnsson, 2015), and it has also been shown that migratory decisions in the fjord are not affected by size (del Villar-Guerra et al, 2014).…”
Section: Re Sultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, an earlier study found that low body condition correlated with increased migration distance in sea trout, potentially for the purpose of maximizing feeding opportunities (Eldøy et al, 2015). Furthermore, home range size has been shown not to correlate with size for trout (Závorka, Aldvén, Näslund, Höjesjö, & Johnsson, 2015), and it has also been shown that migratory decisions in the fjord are not affected by size (del Villar-Guerra et al, 2014). Furthermore, home range size has been shown not to correlate with size for trout (Závorka, Aldvén, Näslund, Höjesjö, & Johnsson, 2015), and it has also been shown that migratory decisions in the fjord are not affected by size (del Villar-Guerra et al, 2014).…”
Section: Re Sultscontrasting
confidence: 99%
“…In addition, there is great variation in habitat use in marine regions, with some sea trout spending most of their time in fjords and some venturing out to the open seas (Bordeleau et al, 2018;del Villar-Guerra, Aarestrup, Skov, & Koed, 2014). Decisions made regarding staying in fjord habitats or moving to the open sea are made shortly after entering the fjord (del Villar-Guerra et al, 2014). Decisions made regarding staying in fjord habitats or moving to the open sea are made shortly after entering the fjord (del Villar-Guerra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The stream runs for several km across agricultural land, where a number of tributaries join in before reaching the Mariager Fjord (56 ∘ 40 ′ N; 10 ∘ 00 ′ W). The stream is home to a large population of semi-anadromous S. trutta (del Villar-Guerra et al, 2014). Three different sites (1-2 km apart) within the same stream were used.…”
Section: Methodsmentioning
confidence: 99%
“…Historically, acoustic tags have been fairly large, which has limited the use of this technology to larger species or adult life stages; however, advances in miniaturization and battery technology have permitted tag manufacturers to create functional tags as small 5 mm diameter and 12 mm in length, weighing 0.65 g (for example, V5, VEMCO, Bedford, Nova Scotia, Canada). These advances have permitted researchers to use acoustic telemetry on earlier life stages such as sub-yearling salmonids [15,16] and smolts [16][17][18].…”
Section: Introductionmentioning
confidence: 99%